2008
DOI: 10.1093/europace/eun383
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular electrophysiology in congestive heart failure and its correlation with heart rate variability and baroreflex sensitivity: a canine model study

Abstract: These results suggest that ventricular electrophysiological characteristics correlated with abnormal autonomic nerve function may have important effects on sudden cardiac death. Further research is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Enhanced neovascularization in mild/moderate heart failure CD31 is a pan-endothelial marker, whereas CD105 preferentially reacts with "newly forming" vessels [16][17][18]. Hence, CD31 was used to assess total MVD and CD105 was used to assess neovascularization in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced neovascularization in mild/moderate heart failure CD31 is a pan-endothelial marker, whereas CD105 preferentially reacts with "newly forming" vessels [16][17][18]. Hence, CD31 was used to assess total MVD and CD105 was used to assess neovascularization in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The method of inducing heart failure has recently been reported in detail previously [17]. Briefly speaking, anesthesia was induced with sodium pentobarbital (30 mg/kg intravenous) and maintained by isoflurane (0.5-1 % in O 2 /N 2 O [1:2]).…”
Section: Animal Modelmentioning
confidence: 99%
“…Similar phenomenon was previously observed in tachycardiomyopathic dogs. However, in a study, conducted by Zhou et al, VERP was determined once, after 4-5 weeks of rapid pacing at 240 bpm [8]. Prolonged VERP and incomplete repolarization may contribute to the development of early after-depolarizations and trigger arrhythmias [9].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a correlation was found between BEI and QTVI. 26 Reduced parasympathetic nervous activity and increased sympathetic nervous activity may contribute both to an increase in QTVI and to a reduction in BEI.…”
Section: Discussionmentioning
confidence: 99%